A RANDOMIZED, DOUBLE-BLIND COMPARISON OF INTRATHECAL NALBUPHINE AND BUPRENORPHINE AS ADJUVANTS TO 1% 2-CHLOROPROCAINE FOR SPINAL ANESTHESIA IN AMBULATORY PERIANAL SURGERY - GOUD, BEEMAGOUNI GNANESHWAR; EDARA, SHOW REDDY; NIKITHA, IAILNENI VENKAT SAI; KIRAN, LAKKAM VAMSEE (International Journal of Current Pharmaceutical Research, 2026)
Objective: Perianal surgeries in ambulatory settings require anesthetic agents with rapid onset, predictable duration, and minimal postoperative morbidity. This study compared the efficacy of Nalbuphine and Buprenorphine as intrathecal adjuvants to 1% 2-Chloroprocaine in spinal anesthesia for day-care perianal surgeries. Methods: In this prospective, randomized, double-blind study, 68 ASA I/II patients aged 18–60 years undergoing elective perianal surgeries were randomized into two groups (n=34 each). Group B received 40 mg 1% 2-Chloroprocaine+Buprenorphine 60 μg; Group N received 40 mg 1% 2-Chloroprocaine+Nalbuphine 0.4 mg. Outcomes included onset and duration of sensory and motor blocks, regression times, postoperative analgesia, hemodynamic stability, and adverse effects. Results: Sensory block onset was faster in Group B (2.6±1.28 min) compared to Group N (3.71±1.0 min, p<0.001). Motor block onset was also faster with Buprenorphine (2.85±1.23 min vs 3.71±1.0 min, p<0.01). Nalbuphine prolonged regression to S2 (71.29±8.66 min vs 66.82±9.27 min, p<0.001) and duration of motor block (64.41±7.86 min vs 59.65±9.74 min, p<0.05). Time to rescue analgesia was longer with Nalbuphine. Hemodynamics remained stable; adverse effects were minimal. Conclusion: Intrathecal Buprenorphine and Nalbuphine are safe and effective adjuvants to 1% 2-Chloroprocaine for spinal anesthesia in day-care perianal surgeries. Buprenorphine ensures faster onset of block, while Nalbuphine provides superior and longer-lasting postoperative analgesia. Both support early ambulation and discharge, making them valuable options in ambulatory anesthesia.